Diseño e implementación de un control de temperatura para una planta de caracterización de fotomultiplicadores de silicio - Baquero Beltrán, Paola Andrea (Universidad Antonio Nariño, 2021)
Silicon photomultipliers (SiPM) are widely used devices which have direct application in various scientific fields, currently the Antonio Nariño University (UAN) finances the Research, Science, Technology and Innovation Project of High Energy Physics in International Cooperations in which is carried out a photodetection work, where SiPM are used, for which they require to know in detail certain characteristics that allow its correct operation. One of the most important characteristics is the gain, which is directly affected with the temperature variation, which generates a response with low reliability. The present work expose the development of an analog integral proportional temperature (PI) automatic control system with which a characterization plant for the SiPM is controlled that allows the temperature to be varied from room temperature to 50 ° C, which stabilizes the system in less than 9 minute with position error less than 5.53%.